Analisis Pengaruh Kualitas Produk, Brand Image, Self-Image, dan Word of Mouth Terhadap Keputusan Pembelian Produk Wardah pada Konsumen Multi-Generasi - Karimah, Zulfathin Salma; Setyorini, Noni; Puspitasari, Ratih Hesty Utami (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the influence of product quality, brand image, self-image, and word of mouth on purchasing decisions of Wardah products among multigenerational consumers in Boja District. This study uses a quantitative approach with a survey method through questionnaires distributed to 150 respondents who are evenly divided into three generational groups, namely Generation X, Millennial Generation, and Generation Z, selected using purposive sampling techniques. Data were analyzed using multiple linear regression and One-Way ANOVA tests with the help of IBM SPSS Statistics software. The results showed that product quality has a positive and significant effect on purchasing decisions (β = 0.195; p < 0.001), brand image has a positive and significant effect (β = 0.199; p = 0.001), self-image has a positive and significant effect (β = 0.278; p < 0.001), and word of mouth has a positive and significant effect (β = 0.145; p < 0.001). Self-image is the variable that has the most dominant influence. Simultaneously, the four independent variables were able to explain 55.4% of the variation in purchasing decisions (R² = 0.554). In addition, the results of the One-Way ANOVA test showed no significant difference in the influence of the four variables on purchasing decisions among Generation X, Millennials, and Generation Z. This finding indicates that generational characteristics are not the main differentiating factor in Wardah product purchasing behavior.